My Future: Psychodrama and Meditation to Improve Well-Being Through the Elaboration of Traumatic Loss Among Italian High School Students - Testoni, Ines; Ronconi, Lucia; Biancalani, Gianmarco; Zottino, Andrea; Wieser, Michael Alexander (Frontiers in Psychology, 2021)
This study was designed as an action-research aimed to help students to elaborate their feelings of traumatic grief, due to a car accident and a suicide of two of their classmates, in an Italian high school. A death education project was realized in order to prevent the Werther effect. The intervention was based on psychodramatic techniques and meditation with Tibetan bells to encourage reflection on the suffering of traumatic loss, the sense of life and their future. A total of 89 students from 4 classes (46 in the experimental group: 2 classes, 43 in the control groups: two classes) participated in the study, among which 82 (45 in the experimental group, 37 in the control group) completed the pre-test and the post-test survey. The intervention consisted of eight two-hour meetings, during which the themes of death and loss were dealt with through theoretical discussions, dramatization and meditation. Two other classes which participated in the assessment as a control group did not attend the activities. The following instruments were used: Death Attitude Profile-Revised, which measures individual attitudes towards death; Psychological Well-being Scale, which measures a person’s psychological well-being; Resilience Scale for Adolescents, which measures the construct of resilience in adolescents; Self-Transcendence Scale, which measures self-transcendence; and Testoni Death Representation Scale, which measures the ontological representations of death. The results demonstrated that in the experimental group, there was a reduction in the fear of death and its avoidance, and that the students normalised the representation of death as something natural, thus improving their well-being. It is consequently possible to say that well-being is not simply the absence of suffering and worries, but rather, is rooted in the possibility of thinking of creative solutions to the trauma.